Cloprostenol treatment of feline open-cervix pyometra - García Mitacek, María Carla (2014)
Treatment with cloprostenol, a prostaglandin synthetic analogue, was evaluated in five queens with open-cervix pyometra. Cloprostenol was administered (5 μg/kg body weight SC) on 3 consecutive days and amoxicillin (20 mg/ kg body weight IM) on 7 consecutive days. Transient post-injection reactions caused by cloprostenol administration included diarrhea, vomiting and vocalizations. Reactions began as quickly as 10 mins after cloprostenol administration and lasted as long as 30 mins. All queens improved clinically after cloprostenol treatment and remained healthy until the end of the study, 1 year after treatment. All queens resumed normal estrous cycles without further treatment and two (40%) delivered a normal litter. In conclusion, use of cloprostenol is an acceptable treatment for opencervix pyometra in queens.